Chronic dermal sinuses as a manifestation of histiocytosis X. Issue 6528 (26th April 1986) - Sacks, S H; Hall, I; Ragge, N; Pritchard, J
Abstract : Two young patients presented with generalised lymphadenopathy, otorrhoea, otitis, and rash. Over the next few years chronically discharging sinuses began to form over enlarged nodes and histological appearances were typical of histiocytosis X. In neither case were micro-organisms isolated from the lesions, and in both patients healing occurred with immunosuppressive agents. Chronic dermal sinus formation secondary to lymph node disease has never before been recorded as a manifestation of histiocytosis X. Histiocytosis X should therefore be considered in the differential diagnosis of "suppurative" lymphadenopathy so that appropriate treatment may be given without delay.